ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL ZMIJEWSKI DAN GROVER PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI - Vina Sulistia Damayanti; Titing Suharti; Diah Yudhawati (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the most accurate model between the zmijewski model and the grover model for financial distress assessment in the transportation and logistics sub-sector in 2019 - 2021. The population of this study is the transportation sub-sector periiode 2019 - 2021 with a total sample of 6 companies. The sample selection procedure in this study was purposive sampling method. The data analysis technique used in this research is descriptive analysis technique. The results of this study are that there are several transportation sub-sector companies and those that have the potential to experience financial distress because they experience poor financial conditions. The results of this study indicate that the calculation of the highest level of accuracy is the zmijewski model, namely with an accuracy level of 38.88% with a type error of 61.11% and the grover model has an accuracy level of 27.77% and has a type error of 72.22%.